Supporting GPs in the Management of Children and Young People with ADHD Through Project ECHO®: Results from a Self-Efficacy Survey - Dana Newcomb; Phil Nixon; Perrin Moss; Vishal Kapoor (International Journal of Integrated Care, 2022)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) accounts for a high proportion of paediatric outpatient visits in Australia. Shared care by general practitioners (GPs) would deliver more timely care, closer to home, however GPs indicated the need for interprofessional training support. This study describes the use of Project ECHO®, a guided practice model, to support GPs with ADHD management, by connecting them virtually with an interprofessional team of paediatric specialists using a structured methodology. Methods: A retrospective pre/post-knowledge and self-efficacy survey across twenty-seven aspects of ADHD management was administered, using a seven-point Likert scale. Results: Significant improvement (p < 0.001) in provider self-efficacy was demonstrated across all tested domains. Discussion: Use of the ECHO model™ by an interprofessional team of paediatric specialists achieved an increase in GP knowledge and self-efficacy in the local management of children and young people with complex healthcare needs. Learnings indicate viability to expand the application of the ECHO model™ to address fragmentation for other priority populations across the Australian healthcare and human service sector landscape. Conclusion: Use of the ECHO model™ to support and train GPs was successful. Integration of care was achieved through strengthened partnerships between content and context experts, and the ECHO model™’s case-based learning methodology.